2010
DOI: 10.1016/j.landurbplan.2010.04.013
|View full text |Cite
|
Sign up to set email alerts
|

The economic impact of tourism in six German national parks

Abstract: a b s t r a c tTourism in protected areas can create considerable income for adjacent communities. Based on faceto-face visitor surveys, the present study measures the structure, size and economic impact of tourist expenditure in the six German national parks Niedersächsisches Wattenmeer, Bayerischer Wald, Eifel, Müritz, Hainich and Kellerwald-Edersee. We find that mean daily expenditure per person of national park visitors is considerably below the national averages for tourists in Germany: day-trippers spend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
98
1
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(113 citation statements)
references
References 20 publications
3
98
1
11
Order By: Relevance
“…It remains the manager's task to understand tourists' preferences and attitudes and to search for efficient management solutions on how to respond to these demands without harming nature. Certainly, a systematic and continuous visitor monitoring system is mandatory [46] within such a challenging process. Veisten et al [39] emphasized that sustainable tourism management can be reached in national parks by adopting an active visitor management system based on monitoring and visitor surveys.…”
Section: Discussionmentioning
confidence: 99%
“…It remains the manager's task to understand tourists' preferences and attitudes and to search for efficient management solutions on how to respond to these demands without harming nature. Certainly, a systematic and continuous visitor monitoring system is mandatory [46] within such a challenging process. Veisten et al [39] emphasized that sustainable tourism management can be reached in national parks by adopting an active visitor management system based on monitoring and visitor surveys.…”
Section: Discussionmentioning
confidence: 99%
“…An important study in 2010 demonstrates the potential opportunities in NPs. Mayer et al (2010) analyses the economic impact of tourism in six German national parks. It shows that the NP is a driver of development and substantial opportunities exist based on the protection and expansion of the non-intervention wilderness areas of high value nature in Šumava NP.…”
Section: Pro-wilderness Development Tourismmentioning
confidence: 99%
“…Experience has shown that it can both create substantial revenue streams for local communities (Mayer et al 2010) and enhance visitors' awareness of ecological issues, if well managed (eagles et al 2002). Both of these fields need more attention in Russia.…”
Section: Neoliberalism: Economisation In the 2010smentioning
confidence: 99%
“…The TEEB initiative, short for The Economics of Ecosystems and Biodiversity, is an international attempt to establish a standard basis for natural capital accounting and thus capture and quantify the value of nature and its conservation. Other studies have sought to measure the economic impact of protected areas (e. g. Mayer 2014; Mayer et al 2010). …”
Section: Introductionmentioning
confidence: 99%